2011
DOI: 10.1002/ejoc.201001596
|View full text |Cite
|
Sign up to set email alerts
|

Easy Routes towards Chiral Lithium Binaphthylamido Catalysts for the Asymmetric Hydroamination of Amino‐1,3‐dienes and Aminoalkenes

Abstract: 1 - ArticleThe preparation of chiral lithium salts of N,N'-disubstituted binaphthyldiamines and their use as catalysts for asymmetric hydroamination/cyclisation of amino-1,3-dienes and aminoalkenes are reported. Several straightforward methods involving the combination of ligand with solutions of methyl- or [(trimethylsilyl) methyl] lithium (LiCH(2)TMS) by ex situ or in situ preparation have been investigated. The use of LiCH(2)TMS in an in situ procedure was revealed as the easiest for carrying out reactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…Still, great progress is highlighted by advances with metallocene-based and axially chiral lanthanide catalysts, alkali metal coordination complexes, and alkaline earth metal catalysts . Breakthroughs in zirconium-catalyzed alkene hydroamination include axially chiral bis(aryloxy), bis(amido), a highly enantioselective bis(amidate) and bis(carboxyamide) complexes (or similar Ta-based systems) as catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Still, great progress is highlighted by advances with metallocene-based and axially chiral lanthanide catalysts, alkali metal coordination complexes, and alkaline earth metal catalysts . Breakthroughs in zirconium-catalyzed alkene hydroamination include axially chiral bis(aryloxy), bis(amido), a highly enantioselective bis(amidate) and bis(carboxyamide) complexes (or similar Ta-based systems) as catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…While there has been interest in enantioselective hydroamination of 1,3-dienes, 14 most studies have focused on intramolecular variants. 15 Prior to our study, Hartwig demonstrated the only example of an enantioselective, intermolecular hydroamination of 1,3-dienes; this study focused on cyclohexadiene. 3 In contrast, enantioselective hydroamination of unsymmetric dienes had yet to be achieved.…”
mentioning
confidence: 99%
“…A few years ago, our group reported the first application of chiral diamidobinaphthyldilithium salts as easily available and efficient alkali‐metal‐based (pre)catalysts for the asymmetric cyclohydroamination of amino‐1,3‐dienes with the highest stereo‐ and enantioselectivities described to date (up to 93:7 dr and 71 % ee ) . The methodology was further extended to the enantioselective intramolecular hydroamination of primary and secondary amines tethered to alkenes at room temperature with ee values up to 58 % . These efficient lithium‐based catalysts were in situ prepared by a straightforward protocol resulting from the combination of N ‐substituted ( R )‐(+)‐1,1′‐binaphthyl‐2,2′‐diamines such as ( R )‐H 2 L 1–3 (Figure ) and LiCH 2 TMS in a 1:2.5 ratio.…”
Section: Methodsmentioning
confidence: 99%